2010
DOI: 10.1088/0953-8984/22/12/125702
|View full text |Cite
|
Sign up to set email alerts
|

Structural properties and superconductivity of SrFe2As2 −xPx(0.0 ≤x≤ 1.0) and CaFe2As2 −yPy(0.0 ≤y≤ 0.3)

Abstract: The SrFe(2)As(2 - x)P(x) (0.0 ≤ x ≤ 1.0) and CaFe(2)As(2 - y)P(y) (0.0 ≤ y ≤ 0.3) materials were prepared by a solid-state reaction method. X-ray diffraction measurements indicate that the single-phase samples can be successfully obtained for SrFe(2)As(2 - x)P(x) (0.0 ≤ x ≤ 0.8) and CaFe(2)As(2 - y)P(y) (0.0 ≤ y ≤ 0.3). Visible contraction of the lattice parameters is determined due to the relatively smaller radius of P ions in comparison with that of As. The spin-density-wave (SDW) instability associated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…4,8 Note that the lattice parameter along the c-axis in Sr122AsP is smaller than that in Ba122AsP due to the ion radius smaller for Sr than for Ba, giving rise to a significant deformation in the Fermi surface topologies. 21 Nevertheless the phase diagram of AFM and SC phases in Sr122AsP 14,16 resembles that in Ba122AsP.…”
mentioning
confidence: 89%
“…4,8 Note that the lattice parameter along the c-axis in Sr122AsP is smaller than that in Ba122AsP due to the ion radius smaller for Sr than for Ba, giving rise to a significant deformation in the Fermi surface topologies. 21 Nevertheless the phase diagram of AFM and SC phases in Sr122AsP 14,16 resembles that in Ba122AsP.…”
mentioning
confidence: 89%
“…Unlike the corresponding arsenides, the Fermi surfaces of the phosphides are very similar to those of the superconducting phases of the Ba and Sr 122 materials. In all three (Ba, Sr, Ca) phosphides superconductivity can be induced by partial substitution of P with isovalent As [32,33] and hence the pure phosphide can be viewed as the end member of these series. The maximum T c produced by P/As substitution is very comparable to that obtained by the non-isovalent dopants K [11] / Co [34] or pressure [35].…”
Section: Phosphides: Bafementioning
confidence: 99%
“…This is a very general property of the Fe-based superconductors and in fact there are only a few examples known where SC does not show up despite vanishing Fe ordering [e.g., Mn-doped LaFeAsO 7 or BaFe 2 As 2 8 ]. In this sense CeFeAs 1−x P x O presents a unique situation because of the following: First, replacing As with P "usually" results in SC as shown for AFe 2 As 2 [A = Ca, 9 Ba, 10 Sr, 9 Eu 11 ] and RFeAsO [R = La, 5 Sm 12 ], and second, CeFeAsO becomes superconducting when substituting Fe with Co 13 or O with F 14 and also by inducing oxygen vacancies. 2 But combining P doping with R = Ce among the RFeAsO compounds results in exceptional behavior: The Fe ordering is suppressed, as shown by de la Cruz et al 15 and Luo et al, 16 however, superconductivity had not yet been observed in CeFeAs 1−x P x O.…”
mentioning
confidence: 99%